Food Insecurity and Sugar-Sweetened Beverage Consumption Among WIC-Enrolled Families in the First 1,000 Days - Fernández, Cristina R. (J Nutr Educ Behav, 2020)
OBJECTIVE. Determine the association between household food insecurity and habitual sugar-sweetened beverage (SSB) consumption among WIC-enrolled families during the first 1,000 days. METHODS. Cross-sectional analysis of pregnant women and mothers of infants under 2 years-old in the Special Supplemental Nutrition Program for Women, Infants and Children (WIC) was performed. Families recruited sequentially at consecutive visits completed food insecurity and beverage intake questionnaires. Estimated logistic regression models controlled for socio-demographic characteristics. RESULTS. Of 394 Hispanic/Latino mothers and 281 infants, 63% had household food insecurity. Food insecurity significantly increased odds of habitual maternal (unadjusted odds ratio (OR)=2.39, 95% CI=1.27–4.47, P=0.01) and infant SSB consumption (OR=2.05, 95% CI=1.15–3.65, P=0.02), and the relationship was not attenuated by maternal age, education, or foreign-born status. CONCLUSIONS AND IMPLICATIONS. Food insecurity increased odds of habitual SSB consumption in WIC families. Interventions to curb SSB consumption among WIC-enrolled families in the first 1,000 days in the context of household food insecurity are needed. (149 words)